Advances in food and nutrition research. - Toldra, Fidel (ISSN, 2023)
Advances in Food and Nutrition Research, Volume 107 provides the latest advances on emerging bioactive compounds with putative health benefits and their controlled release and application in foods and nutraceuticals, as well as information on food technologies, including 3D printing, safety of raw materials, and viruses in foods. Chapters in this new release cover Tackling food allergens - the role of food processing on proteins' allergenicity, Plant bioactive peptides for cardiovascular disease prevention, Caffeine and sport, Nanostructured steady-state nanocarriers for nutrients preservation and delivery, Flavor perception and health benefits of tea, Next Generation Plant-based Meat Alternatives: Sources, manufacturing and consumer acceptance, and more. Other sections cover Bioprotective cultures and bacteriocins as food preservatives and Raman Spectroscopy: principles and recent applications in Food Safety.